An Assessment of the Motorcycle Accident at Barangay Batasan Hills Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The aim of this study is to determine how riders and traffic police assess the accidents inBatasan Hills. Motorcycles are the most numerous vehicles in the Philippines, so it isinevitable that motorcycles also have the most number of accidents. The researcherconducted this study to raise awareness of the possible causes and effects of a motorcycleaccident. What is the response of the traffic police whenever there is an accident, and what isthe condition of the accident victims? The majority of motorcycle riders did not have a legaldriver's license and would prefer to avoid the police. Head injuries, fractures, lacerations, andcontusions were the most common motorcycle injuries. The majority of the incidents werecaused by an unfinished construction road. Motorcycle accidents can be reduced throughincreased law enforcement, public education, the usage of helmets, and good condition ofconstruction roads.According to the twenty-five respondents, motorcycle riders assess the accidents in Batasanin terms of roadways as Unfinished Construction roads. In terms of the drivers, the Destructionof drivers on the road is the main cause of accidents. And in terms of weather conditions, therespondents said sudden use of brakes when it’s raining causes skidding on the road, which isa cause of accidents. According to the respondents, unfinished construction roads are thecommon reason that can cause accidents. Because most of the motorcycle riders didn’t noticethe wrecked road while driving are on the road. In terms of drivers, intoxicated drivers are themost common cause of accidents. In Addition, sudden use of brakes when it’s raining causesskidding on the road.
Keywords: Criminology